Notes on Post-criticality: Towards an Architecture of Reflexive Modernisation - Robert Cowherd (Footprint)
Since around 2002, the performance of critical theory in architecture and the humanities has itself undergone a critical re-evaluation. Authors representing divergent perspectives, from theory’s perennial naysayers to the standard bearers of critical theory themselves, have converged towards a similar conclusion: judged by outcomes, critical theory has proven ineffective at best, and arguably, corrosive to human progress. In architecture, the debate has revolved around the identification of a ‘critical architecture’ in education and production since the 1970s. In apparent rejection of the isolation and purity of critical architecture’s orthodoxy, Rem Koolhaas and others have chosen engagement with the forces (and commissions) of late capitalism to which the term ‘post-criticality’ has been applied.